Analisis Pengaruh Produk, Promosi, Harga dan Saluran Distribusi Terhadap Keputusan Pembelian Kartu Seluler bagi Mahasiswa Di Kota Padang - Nico Pranata Mulya (Universitas Batanghari, 2022)
This study aims to determine and prove how far the influence of Products, Promotions, Prices and Distribution Channels on the purchasing decisions of Cellular Cards for students in the city of Padang. This research was carried out in the city of Padang, the population in this study were students who had cellphones, the sampling technique was Accidental Sampling formula Cochran with a total sample of 384 people. The data collection technique is by using a questionnaire. To see the effect of Product, Promoso, Appreciate and Distribution Channels on the decision to purchase Cellular Cards for students in the city of Padang. The results of this study indicate (1) that the product has a significant effect on purchasing decisions as indicated by the value (Sig. 0.005 < 0.05), (2) the Promotion variable has a significant effect with the indicated value (Sig. 0.000 < 0.05), (3 ) the price variable has a significant effect as indicated by the value (Sig 0.022 < 0.05), (4) the distribution channel variable has a small effect by showing the value (Sig 0.184 > 0.05) but after trimming the value of each variable changes (1) the product has an effect significant effect on purchasing decisions (Sig value 0.000 < 0.05), (2) Promotional variables have a significant effect on purchasing decisions with indicated value (0.000 < 0.05) (3) Price variable has a significant effect on value (Sig 0.019 < 0.05 ) so that the distribution channel factor does not take into consideration in making purchasing decisions. Based on the results of the study, it can be seen that product, promotion and price variables are variables that influence purchasing decisions made by students in the city of Padang.